Penerapan Budaya Baayun Mulud pada Masyarakat Suku Banjar dalam Membentuk Pendidikan Karakter pada Anak - Lia Novianti, Lia Novianti; Rusydi Ananda, Rusydi Ananda; Tabah Hati, Silvia (Jurnal Dirosah Islamiyah, 2024)
This study aims to find out 1) the application of the baayun mulud culture to the Banjar people in shaping character education for children in Kota Rantang Village, 2) the supporting factors in forming character education for children through the baayun mulud culture 3) the inhibiting factors in forming character education for children through the baayun mulud culture in Kota Rantang Village, Hamparan Perak District. The type of research used in this research is descriptive qualitative research. The results of this study indicate that 1) The results of the study indicate that the application of the baayun mulud culture in shaping children's character education in Kota Rantang Village can form religious, honest, tolerant, disciplined and responsible characters in children through the baayun mulud tradition, 2) Supporting factors namely the recitation of prayers, al-barzanji and marhaban prayers which are played to the child during the baby boy. Listening to the chanting of prayers and praise that benefits his memory when he grows up and is supported by parental education. Meanwhile 3) Inhibiting factors are lack of belief in tradition, economic factors as for parents who do not have the costs to attend the baayun mulud event, busy parents, and parenting styles